The subversive heroines of Gyp and their feminist stamp on the Hispanic press at the twilight of the nineteenth century - García Fuentes, Raquel (Filanderas, 2018)
From the last twenty years of the 19th century until the beginning of the next one, a great number of plays would be performed in the French scene and beyond by the French writer Sibylle Gabrielle Marie-Antoinette de Riquetti de Mirabeau (1849-1932), better known as Gyp. Paradoxically, both this theatrical production and her novels, endowed with an obvious feminist consciousness, would fade into oblivion over the years. Therefore, the feminist theater of Gyp and its perception in the Hispanic context will thus be the main research areas of our study, whose themes will be interpreted from a gender perspective.